The incipient denaturation mechanism of DNA. Issue 36 (17th August 2022) - Xu, Min; Dai, Tinghui; Wang, Yanwei; Yang, Guangcan
Abstract : The persistent length of DNA decreases significantly by adding small amount of DMSO. Local DNA denaturation occurs even at very low DMSO concentration, which can be observed by atomic force microscopy directly. Abstract : DNA denaturation is related to many important biological phenomena, such as its replication, transcription and the interaction with some specific proteins for single-stranded DNA. Dimethyl sulfoxide (DMSO) is a common chemical agent for DNA denaturation. In the present study, we investigate quantitatively the effects of different concentrations of DMSO on plasmid and linear DNA denaturation by atomic force microscopy (AFM) and UV spectrophotometry. We found that persistent length of DNA decreases significantly by adding a small amount of DMSO before ensemble DNA denaturation occurs; the persistence length of DNA in 3% DMSO solution decreases to 12 nm from about 50 nm without DMSO in solution. And local DNA denaturation occurs even at very low DMSO concentration (such as 0.1%), which can be directly observed in AFM imaging. Meanwhile, we observed the forming process of DNA contacts between different parts for plasmid DNA with increasing DMSO concentration. We suggest the initial mechanism of DNA denaturation as follows: DNA becomes more flexible due to the partial hydrogen bond braking in the presence of DMSO before local separation of the two complementary nucleotide chains.